PENGARUH DIVERSITAS DAN INKLUSI TERHADAP KINERJA PEGAWAI DIREKTORAT JENDERAL PERDAGANGAN LUAR NEGERI - Brilliansyah, Bintang; Fadili, Dadan A, (Politeknik Negeri Ambon, 2025)
Introduction: This investigation aims to evaluate the impact of diversity and inclusion on the performance of employees at the Directorate General of Foreign Trade. The research is motivated by the observed decrease in performance over the past three years, the presence of generational disparities, and the limited implementation of inclusive practices. Methods: The research employs a quantitative approach incorporating path analysis to investigate the direct and indirect consequences of diversity and inclusion. The Taro Yamane formula was used with random sampling techniques to select 159 civil servants. The data were processed using SPSS to compute correlation coefficients, path coefficients, and hypothesis testing.Results: The results indicate that diversity has a direct effect of 10.6% and an indirect effect of 13.8% through inclusion, resulting in a total influence of 24.4% on employee performance from the findings. Inclusion has a direct impact of 31.3% and an indirect effect of 13.8% through diversity, resulting in a total impact of 45.1%. The R² value of 0.697 confirms that diversity and inclusion jointly account for 69.5% of the variation in employee performance.Conclusion and suggestion: Diversity and inclusion significantly and positively influence employee performance. The research suggests that public sector organizations should adopt inclusive policies and prioritize workforce diversity to improve institutional performance and employee productivity. Keywords: Diversity, Employee Inclusion, Institution, Performance.